2022
DOI: 10.3390/ani12162052
|View full text |Cite
|
Sign up to set email alerts
|

Trait Analysis in Domestic Rabbits (Oryctolagus cuniculus f. domesticus) Using SNP Markers from Genotyping-by-Sequencing Data

Abstract: The domestic rabbit (Oryctolagus cuniculus f. domesticus) is a very important variety in biomedical research and agricultural animal breeding. Due to the different geographical areas in which rabbit breeds originated, and the long history of domestication/artificial breeding, rabbits have experienced strong selection pressure, which has shaped many traits of most rabbit varieties, such as color and weight. An efficient genome-wide single-nucleotide polymorphism (SNP) detection strategy is genotyping-by-sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In our study, GBS fragments have been positioned and their relationship to genic regions under selection has been ascertained. Similarly, recent GWAS studies have successfully revealed candidate genes under selection in camels (Bitaraf et al, 2022), pigs (Chen et al, 2019) and rabbits (Li et al, 2022). The most important selection signal obtained in our results was detected on OAR20 involving 12 SNPs mapped on the genomic region ~50.3–50.6 Mbp.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, GBS fragments have been positioned and their relationship to genic regions under selection has been ascertained. Similarly, recent GWAS studies have successfully revealed candidate genes under selection in camels (Bitaraf et al, 2022), pigs (Chen et al, 2019) and rabbits (Li et al, 2022). The most important selection signal obtained in our results was detected on OAR20 involving 12 SNPs mapped on the genomic region ~50.3–50.6 Mbp.…”
Section: Discussionmentioning
confidence: 97%